2021
DOI: 10.1371/journal.pone.0244302
|View full text |Cite
|
Sign up to set email alerts
|

Insights into mobile health application market via a content analysis of marketplace data with machine learning

Abstract: Background Despite the benefits offered by an abundance of health applications promoted on app marketplaces (e.g., Google Play Store), the wide adoption of mobile health and e-health apps is yet to come. Objective This study aims to investigate the current landscape of smartphone apps that focus on improving and sustaining health and wellbeing. Understanding the categories that popular apps focus on and the relevant features provided to users, which lead to higher user scores and downloads will offer insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…In-app purchases permit the user to purchase added services from within an app, and 5 apps considered in this study had this feature [ 49 - 52 , 54 ]. Remarkably, in-app purchase options work well in promoting health apps wherein the essential functions are offered freely [ 73 ]. However, the intention to upgrade to a paid subscription is driven by the subscription features, benefits, and price value [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…In-app purchases permit the user to purchase added services from within an app, and 5 apps considered in this study had this feature [ 49 - 52 , 54 ]. Remarkably, in-app purchase options work well in promoting health apps wherein the essential functions are offered freely [ 73 ]. However, the intention to upgrade to a paid subscription is driven by the subscription features, benefits, and price value [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we first collected the information available in the app marketplace descriptions (eg, number of downloads and user ratings) before downloading the apps and analyzing their content in detail. This strategy differs from those of other recent studies, in which a greater number of apps were identified but where the analysis was limited to the marketplace description [ 8 , 18 , 19 , 38 ]. Among our main findings, we can highlight that 22% (11/49) of the apps were not developed by health care professionals.…”
Section: Discussionmentioning
confidence: 99%
“…We collected the following information from the download platforms: app name, operating system (Android, iOS, or both), developer affiliation, country of origin, language, category, cost, publication date, date of last update, size, version, number of downloads, and user ratings. These indicators are commonly used in studies on health-related apps [ 16 - 19 ]. The overall mean weighted user rating was calculated by considering the number of ratings from both app stores.…”
Section: Methodsmentioning
confidence: 99%
“…These controls can include enabling data encryption or data masking software, which would provide more confidentiality since data becomes difficult to read for unauthorized users. Besides integrating these controls into its app designs, Felicity can also mention its privacy policy through marketing measures to increase app users [4]. Ensuring data privacy and security will benefit Felicity since consumers are more likely to engage and be attracted to applications with secure databases.…”
Section: Data Securitymentioning
confidence: 99%